PERAN KOMISI NASIONAL PERLINDUNGAN ANAK DALAM PERLINDUNGAN ANAK TERHADAP KASUS KEKERASAN SEKSUAL DI DKI JAKARTA TAHUN 2014-2015 - enggal chesar ayoganata; susilo utomo; nur hidayat sardini (Journal of Politic and Government Studies, 2016)
DKI Jakarta is one of province in Indonesia which has highest number for sexual violence for kids in Indonesia, but DKI Jakarta Government has not been able to manage this problem yet. National Child Protection Commission is LSM which focuses in child protection that is caused of inoptimal Government in handling Child problems in sexual violence cases which every year the total cases are increasing. National Child Protection Commission has independent principle, public responsibility, sets the opportunity and chance out to the child in participating by respecting and taking side on child’s basic principle.Method that isused in this research is qualitative research method by desrctiptive approach through direct monitoring in field and legal documents from Central Data and Information of National Child Protection Commission. Technique of data collecting by interviewing National Child Protection Commission and the victim’s family of sexual violence which becomes National Child Protection Commission’s client and monitoring, then it is analyzed qualitatively. Efforts from National Child Protection Commission in handling the victim of sexual violence consist of psychological service and advocation service.Results of this research shows that the existence of National Child Protection Commission has important role for its efforts in sexual violence for child protection in DKI Jakarta though there is still perceived less optimal which is caused of obstacles and limits which are had and faced by National Child Protection Commission. This research also take an important role in role of child protection in National scale.Keywords : child protection, sexual violence, National Child Protection Commission